Fabrication of Ferroelectric Gate Thin‐Film Transistors with a Lanthanum‐Doped HZO Gate Insulator and Indium‐Tin‐Oxide Channel via a Solution Process. Issue 10 (6th May 2022) - Mohit,; Murakami, Tatsuya; Tokumitsu, Eisuke
Abstract : In recent years, lanthanum‐doped hafnium–zirconium dioxide (La‐HZO) has garnered attention as a material for application in ferroelectric devices; moreover, atomic layer deposition has been applied to prepare La‐HZO films with metal–ferroelectric–metal structures. This article describes the fabrication of ferroelectric La‐HZO thin films on Pt/Ti/SiO2 /Si substrates via a solution process. The dependence of the electrical properties on the La concentration of La‐HZO films annealed at 800 °C in vacuum is also discussed. The film with a La concentration of 8 at% exhibits the highest remanent polarization, whereas undoped HZO exhibits paraelectric behavior. Additionally, the leakage current of La‐HZO specimens tends to be significantly lower than that of undoped HZO. Furthermore, a higher annealing temperature corresponds to better ferroelectric properties and a lower leakage current. The characterization of fabricated ferroelectric gate thin‐film transistors (FGTs) with an 8 at% La‐HZO gate insulator and indium‐tin‐oxide channel is shown to confirm typical n ‐channel transistor operation, i.e., a counterclockwise hysteresis loop in the transfer curve; this is attributable to the ferroelectric nature of the La‐HZO gate insulator. The results demonstrate that the proposed FGT design offers a low subthreshold voltage swing, high on/off drain current ratio of 10 6, large on‐current, and large memory window. Abstract : Herein, the dependence of La content on ferroelectric properties of hafnium–zirconium dioxide (HZO) is demonstrated. In addition, the effect of higher crystallization temperature on chemical solution deposition (CSD) lanthanum‐doped HZO (La‐HZO) is clearly shown. Later, high‐performance ferroelectric gate transistors are realized using CSD La‐HZO as gate insulator and CSD indium‐tin‐oxide (ITO) channel.